2016
DOI: 10.1016/j.bpj.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Properties of Lipid A from Various Gram-Negative Bacteria

Abstract: Lipid A is the lipid anchor of a lipopolysaccharide in the outer leaflet of the outer membrane of Gram-negative bacteria. In general, lipid A consists of two phosphorylated N-acetyl glucosamine and several acyl chains that are directly linked to the two sugars. Depending on the bacterial species and environments, the acyl chain number and length vary, and lipid A can be chemically modified with phosphoethanolamine, aminoarabinose, or glycine residues, which are key to bacterial pathogenesis. In this work, homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(151 citation statements)
references
References 81 publications
12
137
0
2
Order By: Relevance
“…Similarly, PAL5 values (139.17–143.55 Å 2 ) are in agreement with measurements of Lipid A at the liquid crystalline state (125–142 Å 2 ) for P. aeruginosa and other related species . Finally, it should be noted that the simulation results of all Lipid A variants are in agreement with previous simulation evidence for the CHARMM36, MARTINI and GROMOS force fields. Overall, these results show that the Lipid A topologies and simulation systems offered by GNOMM are, in terms of lipid bilayer properties, valid and consistent among different levels of resolution.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, PAL5 values (139.17–143.55 Å 2 ) are in agreement with measurements of Lipid A at the liquid crystalline state (125–142 Å 2 ) for P. aeruginosa and other related species . Finally, it should be noted that the simulation results of all Lipid A variants are in agreement with previous simulation evidence for the CHARMM36, MARTINI and GROMOS force fields. Overall, these results show that the Lipid A topologies and simulation systems offered by GNOMM are, in terms of lipid bilayer properties, valid and consistent among different levels of resolution.…”
Section: Resultssupporting
confidence: 88%
“…These include variations of Lipid A from four different species ( E. coli , Pseudomonas aeruginosa , Helicobacter pylori and Neisseria meningitidis ) (Supporting Information Fig. S1), as well as three experimentally studied LPSs, containing Lipid A and the oligosaccharide core (Re and Ra LPS for E. coli and PAO1 LPS for P. aeruginosa ) . In addition, a number of standard lipids are also offered, representing the major categories most commonly found in bacteria .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, the C36 FF allows to accurately represent bilayer properties of fully saturated and monounsaturated lipid molecules in the NpT ensemble. 73 In the last years, different kind of lipids were added to C36 using the same parameter strategy, such as a variety of acyl chains (PUFAs, 123 branched 124 chains and chains with cyclic moieties 125 ) and head groups (PA, PG, PI, and PS), 72,126,127 sterols (cholesterol, 128 ergosterol 129 and plant sterols 130 ), sphingolipids 131 and ceramides 132 as well as glycolipids 133 and LPS 126,134 making use of the CHARMM carbohydrate FF.…”
Section: Charmmmentioning
confidence: 99%
“…26,27 Im and co-workers provided a comparison of the properties of bilayers composed of several different lipid A types. 28 At the CG level, we are only aware of models of LPS molecules developed within the framework of the popular MARTINI force-field. 14 In one recent study, the ability of pristine fullerenes to penetrate the outer membrane was found to be dependent upon the presence of phospholipids in the outer leaflet as well as the inner leaflet.…”
mentioning
confidence: 99%